Sustained delivery of anti-VEGFs from thermogel depots inhibits angiogenesis without the need for multiple injections. (22nd August 2019) - Xue, Kun; Zhao, Xinxin; Zhang, Zhongxing; Qiu, Beiying; Tan, Queenie Shu Woon; Ong, Kok Haur; Liu, Zengping; Parikh, Bhav Harshad; Barathi, Veluchamy Amutha; Yu, Weimiao; Wang, Xiaomeng; Lingam, Gopal; et al.
Abstract : Polyurethane thermogels show sustained delivery of bioactive anti-VEGFs therapeutics to the eye. Abstract : Anti-vascular endothelial growth factor (anti-VEGF) proteins are the gold-standard treatment for posterior eye segment proliferative vascular diseases such as Age-Related Macular Degeneration (AMD) and Diabetic Retinopathy (DR). However, the standard of care requires inconvenient monthly intravitreal injections. This underlies an unmet clinical need to develop alternative solutions for sustained delivery of biologics. In this paper, we demonstrated that anti-VEGFs can be encapsulated by a simple mild process into our polyurethane thermogel depots. By changing the hydrophilic–hydrophobic balance in the copolymer, anti-VEGF release rates can be modulated. The antibody in the thermogel partitions into protein domains which vary in size corresponding to the hydrophilicity balance of the polymer. Anti-VEGFs can be released in a relatively linear manner from the thermogel for up to 40 days in vitro . The encapsulated anti-VEGFs demonstrate anti-angiogenic bioactivity by inhibiting vessel outgrowth in rat ex vivo choroidal explants, and reducing vascular leakage in a VEGF-driven neovascularization rabbit model. In conclusion, we show that these thermogels can be tuned in terms of hydrophilicity and used for sustained delivery of bioactive anti-VEGFs. Physically cross-linked polyurethane thermoresponsive hydrogels could be a promising platform for sustained delivery of biologically active therapeutic proteins.